2018
DOI: 10.1063/1.5021791
|View full text |Cite
|
Sign up to set email alerts
|

Doubling the quality factor of cantilevers in liquid through fluid coupling-based actuation

Abstract: Dynamic-mode cantilevers are a promising tool for real-time biosensing applications due to their high sensitivity and ability to perform label-free measurements. However, operating dynamic-mode cantilevers in liquid is challenging since viscous damping greatly reduces their quality factor and thus limit of detection. We reasoned through physical analysis that if the motion of the surrounding fluid is driven by an external force and not by the sensing cantilever itself, then the dissipative fluid force on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The reliability of the sensor model under hydrodynamic influences is established by comparing the predictions from equations ( 7) and ( 8) with the available experimental results as shown by the examples in tables 1 and 2 and figure 1. There is a 3-4 times reduction in the cantilever resonance frequency in water from the lossless vacuum state to the liquid immersed state for different conditions on the gap-to-width ratio (H ≈ 0.3 − 1.0) [28,62,69]. The major contribution to this reduction comes from the added mass effect; table 2.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reliability of the sensor model under hydrodynamic influences is established by comparing the predictions from equations ( 7) and ( 8) with the available experimental results as shown by the examples in tables 1 and 2 and figure 1. There is a 3-4 times reduction in the cantilever resonance frequency in water from the lossless vacuum state to the liquid immersed state for different conditions on the gap-to-width ratio (H ≈ 0.3 − 1.0) [28,62,69]. The major contribution to this reduction comes from the added mass effect; table 2.…”
Section: Discussionmentioning
confidence: 97%
“…In some studies, damping nonlinearity under large amplitude oscillation conditions and driving cantilever above resonance have been exploited for improving Q-factor [25][26][27]. Leahy and Lai [28] reported that instead of actuating directly, if the cantilever is actuated via liquid coupling the quality factor is improved by a factor of 2. In a recent review, Miller et al [29] summarized research on a variety of pumping mechanisms (including electrical feedback oscillators) for controlling Q-factor of MEMS oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…However, to achieve a good AFM resolution, noise sources must be reduced as much as possible, since the lowest signal level that can be considered as a valid information must be not mixed up with external noise. In spite of this, the cantilever thermal motion is also utilized to calibrate the cantilever's spring constant and to extract the resonance frequencies and quality factors of its resonances as well . Indeed, although novel methods are being developed, most of the times the AFM cantilever calibration is made by means of the thermal noise spectrum method.…”
Section: Introductionmentioning
confidence: 99%